2022
DOI: 10.1002/jcp.30686
|View full text |Cite
|
Sign up to set email alerts
|

USP5 promotes breast cancer cell proliferation and metastasis by stabilizing HIF2α

Abstract: Hypoxia‐inducible factor 2α (HIF2α) plays a pivotal role in breast tumor growth and metastasis. However, the regulatory mechanisms of HIF2α protein stability remain poorly understood. The precise role of the deubiquitinase (DUB) ubiquitin‐specific peptidase 5 (USP5) in breast cancer and the underlying mechanism remains largely unknown. Here, we identified USP5 as a novel DUB for HIF2α. Physically, USP5 interacts with HIF2α and protects HIF2α from ubiquitin‐proteasome degradation, thereby promoting the transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…In addition, we further analyzed the association between the expression level of USP5 and DSS or PFI of cancer patients, and we proved that on the whole, USP5 exhibited risk role in MESO and UVM for OS, DSS and PFI, in LUAD and SKCM for OS and DSS and in COAD for DSS and PFI. In addition to the previous reported negative association between USP5 and the progression of BRCA [13], BLCA [27], CRC[28], GBM [21], LIHC [17], melanoma [29], NSCLC [15,26], OV [22] and PAAD [23], our result rst showed that USP5 may emerge as a novel biomarker for predicting the prognosis of ACC, LAML and MESO, especially MESO. These results suggested that USP5 had important diagnostic and prognostic implications in various cancers, and may serve as a therapeutic target for precision oncology.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In addition, we further analyzed the association between the expression level of USP5 and DSS or PFI of cancer patients, and we proved that on the whole, USP5 exhibited risk role in MESO and UVM for OS, DSS and PFI, in LUAD and SKCM for OS and DSS and in COAD for DSS and PFI. In addition to the previous reported negative association between USP5 and the progression of BRCA [13], BLCA [27], CRC[28], GBM [21], LIHC [17], melanoma [29], NSCLC [15,26], OV [22] and PAAD [23], our result rst showed that USP5 may emerge as a novel biomarker for predicting the prognosis of ACC, LAML and MESO, especially MESO. These results suggested that USP5 had important diagnostic and prognostic implications in various cancers, and may serve as a therapeutic target for precision oncology.…”
Section: Discussionsupporting
confidence: 79%
“…Based on our results, USP5 had a certain diagnostic accuracy (AUC > 0.7) in 20 cancer types, especially in predicting BRCA, CHOL, DLBC, LGG, LUSC, PAAD and THYM (AUC > 0.9), indicating the potential clinical application value of USP5 as a reliable diagnostic biomarker. Meanwhile, as a unique member of DUBs, USP5 could regulate the stability of some key tumor-regulating molecular such as, HIF2α in BRCA [13], CyclinD1 in GBM [21], SLUG in LIHC [17], HDAC2 in OV [22], STAT3 [23], WT1 [20] and FOXM1 [24] in PAAD and β-catenin [25], PD-L1[26] and CCND1 [15] in NSCLC to promote cancer progression, and our ROC curve analysis showed the AUC of 0.905 in BRCA, 0.852 in GBM, 0.891 in LIHC, 0.820 in OV, 0.980 in PAAD and 0.946 in LUSC. Thus, the combination of USP5 with these tumor-related molecular separately may signi cantly improve the diagnostic accuracy for the above cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like other USP family deubiquitination enzymes, USP5 is involved in the occurrence and development of various cancers. It has been reported that USP5 overexpressed in many tumors and implicated in its progression, including pancreatic cancer [ 6 ], breast cancer [ 7 ], and glioblastoma [ 8 ]. Wang S et al found that USP5 protein has five key domains, including the implicit ZnF domain and c-box domain, that interact with c-Maf, demonstrating that c-Maf is a crucial factor in USP5-mediated myeloma cell proliferation and survival [ 9 ].…”
Section: Introductionmentioning
confidence: 99%